Efisiensi Penghilangan Polutan Limbah Cair Rumah Sakit X melalui Instalasi Pengolahan Air Limbah - Auliya, Fransisca Nanda; Nurvita Cundaningsih (Jurnal Serambi Engineering, 2025)
Hospitals contain wastewater containing toxic chemicals and radioactive substances. Hospital waste produces liquid waste that is processed physically, chemically, and biologically using IPAL. The purpose of this study was to analyze the efficiency of pollutant removal from hospital liquid waste at the Wastewater Treatment Plant through document reporting at the Environmental Service of Gresik Regency. This study was conducted using a quantitative method with descriptive analysis to analyze the efficiency of the Hospital X IPAL system, through wastewater quality data at the inlet and outlet of wastewater treatment. The average TSS efficiency results were 88.15%, BOD 84.13%, COD 81.62%, Ammonia (NH3-N) 69.82%, Oil and Fat 82.93%, and Total Coliform 75.97%. The performance of the IPAL unit is said to be good where the Hospital X IPAL is effective in processing liquid waste because it can remove pollutant levels and achieve quality standards according to regulations in the Regulation of the Minister of Environment and Forestry No. 68 of 2016 concerning Domestic Wastewater.